Bimbingan Teknis Penyusunan Daftar Pemilih Bagi PPS Dalam Menghadapi Pemilu 2024 Di Kecamatan Lasalimu Selatan - Nastia Nastia; Syahru Ramadhan; Rahmatia Rahmatia; Muh. Arham; Liyanti Liyanti (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
It is important to remember that the fact that there are many people who have not registered on the Permanent Voters List (DPT) indicates that the quality of the voters list is low. Conversely, the fact that fewer voters are not registered on the DPT indicates that the quality of the voters list is better, even though it is not categorised as good. So that in facing the 2024 Election, it is necessary to ensure readiness in its implementation, one of which is by conducting Technical Guidance for officers who are directly related as the spearhead of the validity of Voter data. The methods used are lectures and discussions, the results obtained from PKM are that officers get information and knowledge in updating voter data so that problems that often occur in organising elections do not recur.